2017
DOI: 10.1016/j.it.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes, DAMPs and miRNA: Features of Stress Physiology and Immune Homeostasis

Abstract: Psychological/physical stressors and local tissue damage increase inflammatory proteins in tissues and blood in humans and animals, in the absence of pathogenic disease. Stress-evoked cytokine/chemokine responses or “sterile inflammation”, can facilitate host survival and/or negatively impact health, depending on context. Recent evidence supports the hypothesis that systemic stress-evoked sterile inflammation is initiated by the sympathetic nervous system, resulting in the elevation of exosome-associated immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
0
9

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(145 citation statements)
references
References 85 publications
3
133
0
9
Order By: Relevance
“…Exosomal miR‐29a was also found to be upregulated in the blood of irritable bowel syndrome (IBS) patients . Immunomodulatory miRNAs including the let‐7 family, miR‐21‐5p, miR‐26a, miR‐92a, miR‐126‐3p, and miR‐451a were found to be enriched in exosomes isolated from the blood . In alcoholic hepatitis, serum exosomes contain increased levels of miR‐122, and could increase secretion of pro‐inflammatory cytokines in treated monocytes .…”
Section: Role Of Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomal miR‐29a was also found to be upregulated in the blood of irritable bowel syndrome (IBS) patients . Immunomodulatory miRNAs including the let‐7 family, miR‐21‐5p, miR‐26a, miR‐92a, miR‐126‐3p, and miR‐451a were found to be enriched in exosomes isolated from the blood . In alcoholic hepatitis, serum exosomes contain increased levels of miR‐122, and could increase secretion of pro‐inflammatory cytokines in treated monocytes .…”
Section: Role Of Exosomesmentioning
confidence: 99%
“…[49] Im-munomodulatory miRNAs including the let-7 family, miR-21-5p, miR-26a, miR-92a, miR-126-3p, and miR-451a were found to be enriched in exosomes isolated from the blood. [50] In alcoholic hepatitis, serum exosomes contain increased levels of miR-122, and could increase secretion of pro-inflammatory cytokines in treated monocytes. [51] In addition to inducing pro-inflammatory effects, exosomal miRNAs can also be anti-inflammatory.…”
Section: Micrornasmentioning
confidence: 99%
“…In addition, immune or behavioral manipulations performed at stages of development that range from the perinatal period, adolescence, and adulthood until senescence, indicate that the impact of behavior–immune interactions is age‐ and sex‐dependent. It is beyond the scope of this article to review the extremely abundant literature dealing with one or the other aspect of this broad subject, and only a few articles from the many available are mentioned here . These reviews also include a large list of references to which the reader interested in a given aspect is referred to.…”
Section: Immunity and Behaviormentioning
confidence: 99%
“…Cells under stress or injury release EVs containing DAMPs, which can contribute to tissue inflammation. Newly identified DAMPs include extracellular heat shock proteins (eHsp72), uric acid crystals, mitochondrial DNA (mtDNA), endogenous RNAs, high mobility group box (HMGB)1 and ATP . Histones are the protein component of nucleosomes, which are the important DAMPs in tissue injury.…”
Section: Biological Functions Of Evsmentioning
confidence: 99%
“…Among EVs, exosomes are the fraction that is enriched in genetic material, mostly non‐coding RNAs. In addition to bounding to protective proteins, such as high‐density lipoprotein and argonaute protein, miRNAs were packaged into protective exosomes . Since the first study reported in 2007, increasing studies showed that exosomes carry miRNA and can transfer functionality to a recipient cell in different disease status.…”
Section: Biological Functions Of Evsmentioning
confidence: 99%